2013
DOI: 10.1002/pssa.201330317
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of sensitivity enhancement in dielectric multilayer surface plasmon sensor

Abstract: Improving the sensitivity of surface plasmon resonance using a multilayer system within the Kretschmann configuration is investigated. In the present study, an alternative approach is proposed to improve the sensitivity of the conventional SPR based on a silver layer, by an additional dielectric nanolayer of SiO 2 , MgO, and TiO 2 over the silver/silicon layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…The integrals of the maximal electric field (S) for single gold layer, bimetallic film and single silver layer SPR sensors are 44.14, 43.34 and 38.69, respectively. This result confirms the statement of correlation between the sensitivity and the electric field integral as described by Benkabou et al [26].…”
Section: Numerical Calculation Results and Analysissupporting
confidence: 92%
“…The integrals of the maximal electric field (S) for single gold layer, bimetallic film and single silver layer SPR sensors are 44.14, 43.34 and 38.69, respectively. This result confirms the statement of correlation between the sensitivity and the electric field integral as described by Benkabou et al [26].…”
Section: Numerical Calculation Results and Analysissupporting
confidence: 92%
“…Shukla et al [ 14 ] and Bao et al [ 15 ] both demonstrated that the sensitivity of an SPR sensor could be increased by adding a ZnO thin film. Besides, Benkabou et al [ 16 ] achieved sensitivity enhancement by employing the dielectric multilayer structure in the SPR sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Refractive index (n) Extinction coefficient (k) References SF-11L glass 1.73205 0 [14] Ag 0.13 3.99 [14] Si 3.92 0.01 [14] AlAs 3.112 0 [15] TiO 2 2.2789 0 [18] Si 3 N 4 2.019 0 [15] Water 1.33 0 [14] Figure 3. Sensitivity as a function of dielectric film thickness for the NGWSPR sensor with Si, AlAs, TiO 2 , or Si 3 N 4 film.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, Shukla et al [16] and Bao et al [17] demonstrated a top ZnO layer is effective in enhancing the sensitivity of a fiber-type and prismtype SPR sensor respectively. Benkabou et al [18] achieved the sensitivity enhancement by employing a dielectric multilayer structure in a SPR sensor.…”
Section: Introductionmentioning
confidence: 99%